IMPLEMENTATION OF LAND LEASE AGREEMENT MANAGED BY PT. INDONESIAN RAILWAYS IN THE OPERATING AREA 4 SEMARANG - Evira Damayanti (LAW FACULTY UNISSULA, 2021)
The right to control from the state over land originates from the right of the Indonesian nation to land, which in essence is an assignment to carry out the duties of the nation's authority which contain elements of public law. PT. Kereta Api Indonesia (Persero) may diversify its business by utilizing its land in collaboration with third parties to support its main business. The purpose of this research is to determine the implementation procedure, the form of land lease agreements to the settlement of land lease defaults managed by PT. Kereta Api Indonesia (Persero) Operation Area 4 Semarang. This research is a sociological juridical research. The results of this research indicate that the implementation of the land lease agreement managed by PT. Kereta Api Indonesia (Persero) is carried out by submitting an application to the Executive Vice President of Daop 4 Semarang. If the contents of the contract have been agreed upon by both parties, the contract is made in 2 (two) copies and signed by both parties on a stamp duty. The form and content of the lease agreement is standard in nature, the contents of which are an agreement of two or more parties or a reciprocal standard agreement. Efforts made by PT. Kereta Api Indonesia (Persero) if there is default, but the contract period has expired and does not make an extension if 2 (two) months before the due date the tenant has not made an application letter for contract extension, the Asset Management Manager makes a notification letter to the tenant that the contract will end and concerned in order to complete the contract extension process.